PĂDUREA, CADASTRUL ŞI MEDIUL ÎNCONJURĂTOR (PANGEEA, 2025)
Forest, Survey and Environment. It is said, not without reason, that forests are the country face. So cumsunt silent, they say lasting truths about man and his relationship with nature around him. The great civilizations that emerged over human history have been built, wood forests in their flowering periods.